Pendidikan Vokasi BTEC UK di Indonesia: Studi Fenomenologi Esensi Pengalaman Peserta Didik - Jang, Johan; Purwanto, Agus; Purnamasari, Dian; Ramdan, Mohamad; Hutagalung, Leo; Akuba, Stefy Falentino; Sulistiyadi, Andi; Pramono, Rudy; Bernarto, Innocentius (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
Studying abroad, including in the United Kingdom is one of the aspirations for students and parents in Indonesia. In comparison to directly continuing study overseas, the availability of BTEC UK curriculum in Indonesia allows students to study for 20 months then continued their final year in the country they are planning to go to, including in the UK. Unfortunately, there is no record of the experience of students undergoing this curriculum in Indonesia, even though the curriculum already exists in Indonesia for more than ten years. This study then explores the motivations behind the decisions of students undergoing the BTEC curriculum in Indonesia, their experiences and the outcomes that occur after. Interviews with the 7 BTEC alumni in Indonesia were conducted and analyzed using qualitative phenomenology study. The results obtained that internal motivation is the main trigger whereas external motivation also applies, which is built up through social influence. The experience felt at the beginning was generally difficult to follow because the students were not used to the system, even though some felt excited about the curriculum learning system. In the middle and end of the semester, some of them feel more accustomed to it while some still find it difficult to follow this curriculum. The results in the form of a variety of positive attitudes including courage, self-confidence, and the development of communication skills.